2001
DOI: 10.1038/sj.onc.1204168
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of NF-κB sensitizes human pancreatic carcinoma cells to apoptosis induced by etoposide (VP16) or doxorubicin

Abstract: The transcription factor NF-kB has anti-apoptotic properties and may confer chemoresistance to cancer cells. Here, we describe human pancreatic carcinoma cell lines that di er in the responsiveness to the topoisomerase-2 inhibitors VP16 (20 mM) and doxorubicin (0.3 mM): Highly sensitive BxPC-3 and PT45-P1 cells, and Capan-1 and A818-4 cells that were almost resistant to both anti cancer drugs. VP16, but not doxorubicin, transiently induced NF-kB activity in all cell lines, whereas basal NF-kB binding was nearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
148
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(155 citation statements)
references
References 28 publications
7
148
0
Order By: Relevance
“…In line with these data, we have shown that NF-kB inhibition may be a strategy to increase sensitivity to Etoposide-induced apoptosis in a cell line derived from a CML blast crisis. We have first shown that Etoposide, which is extensively used in the therapy of myeloid leukemias, activates NF-kB in K562 cell line, as it has been described in pancreatic cancer cell lines [21][22][23]. Interestingly, the kinetic of activation is sensibly different to that observed with the traditional NF-kB activator, TNF-a.…”
Section: Discussionmentioning
confidence: 89%
“…In line with these data, we have shown that NF-kB inhibition may be a strategy to increase sensitivity to Etoposide-induced apoptosis in a cell line derived from a CML blast crisis. We have first shown that Etoposide, which is extensively used in the therapy of myeloid leukemias, activates NF-kB in K562 cell line, as it has been described in pancreatic cancer cell lines [21][22][23]. Interestingly, the kinetic of activation is sensibly different to that observed with the traditional NF-kB activator, TNF-a.…”
Section: Discussionmentioning
confidence: 89%
“…The observation that patients overexpressing RelA show a dramatically decreased survival time may allow stratifying patients into two subgroups: one subgroup is likely to benefit from NF-kB-inhibiting agents and another subgroup which has a relatively good survival perspective irrespective of such a treatment, potentially because resistance to conventional chemotherapeutics due to NF-kB activation has not occurred yet (Arlt et al, 2001(Arlt et al, , 2003. This possibility should be considered when clinical trials with NF-kB-inhibiting agents are being planned.…”
Section: Shuklamentioning
confidence: 99%
“…In another study, NF-kB was found to be activated in a number of pancreatic cancer cell lines, which was later linked to chemotherapy resistance (Arlt et al, 2001(Arlt et al, , 2003. Consequently, inhibition of NF-kB activation in these cell lines using sulfasalazine or the proteasome inhibitor MG-132 resulted in their sensitisation to etoposide, doxorubicin (Arlt et al, 2001) and gemcitabine (Arlt et al, 2003). More recently, overexpression of several NF-kB subunits was described in the cytoplasm as well as in the nucleus of the pancreatic adenocarcinoma cell lines Panc-1 and BxPC-3 (Chandler et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most chemotherapy and radiation treatments induce apoptosis (programmed cell death) in tumor cells, 1,2 and apoptosis also seems to be the main mechanism behind the cell kill induced by a number of cytokines, such as tumor necrosis factor-␣ (TNF-␣). 3,4 However, TNF-␣, chemotherapy, radiation as well as other stimuli activate the transcriptional nuclear factor-B (NF-B), which suppresses the apoptotic potential of these stimuli in vitro.…”
mentioning
confidence: 99%